Application of PSAK 73 on Leases to Financial Performance in Transportation Service Companies listed on the Indonesia Stock Exchange: Penerapan PSAK 73 Atas Sewa Terhadap Kinerja Keuangan Pada Perusahaan Jasa Transportasi yang terdaftar di Bursa Efek Indonesia - Rahayu, Duwi; Rahmawati, Imelda Dian; Hanif, Aisha (Procedia of Social Sciences and Humanities, 2022)
This study aims to determine the application of PSAK 73 on leases to the financial performance of transportation service companies listed on the Indonesian stock exchange. This study uses a quantitative descriptive method to assess the company's performance before and after the application of PSAK 73. The quantitative descriptive method in this study uses secondary data and information from the financial statements of transportation service companies listed on the Indonesian stock exchange that present periodic financial reports in 2018, 2019 and 2020 sourced from www.idx.co.id. The sample used in this study were 3 transportation companies, this is based on available data, namely the company with the largest total shares outstanding on the Indonesian stock exchange. The results of this study indicate that the application of PSAK 73 on leases has an effect on the financial performance of transportation service companies listed on the Indonesian stock exchange which can be seen in the company's statement of financial position. However, the application of PSAK 73 is not fully able to improve the financial performance of transportation service companies due to an increase in the Solvency ratio as measured by the Debt to Asset Ratio (DAR). This is also due to the recognition of Right to Use Assets and Lease Liability which can result in an increase in the company's total liabilities. This study recommends companies to establish policies to reduce the risk of implementing PSAK 73 in transportation service companies.